Top‐Down and Bottom‐Up Processes Jointly Explain Mesopredator Movement and Foraging Ecology - Katie R. N. Florko; Tyler R. Ross; Steven H. Ferguson; Joseph M. Northrup; Martyn E. Obbard; Gregory W. Thiemann; David J. Yurkowski; Marie Auger‐Méthé (Ecology Letters, 2026)
Prey availability and predation risk drive animal distribution, movement, and foraging ecology, yet studies rarely analyse multiple predator–prey levels together. Understanding how predators optimise risk–reward tradeoffs is important for species conservation and management, especially in systems facing extreme ecosystem change. We examined how top‐down (modelled polar bear habitat selection) and bottom‐up (modelled fish diversity) processes influence the habitat selection, movement, and foraging behaviour of 26 ringed seals (greater than 70,000 dives and 10,000 locations over 877 seal days). Our results suggest that polar bears spatially restrict seal movements and reduce the time seals spend foraging, potentially decreasing foraging success. Seals were more likely to be present and dive longer in high‐predation risk areas when prey diversity was high. Further, seal habitat selection models excluding polar bears overestimated core space use. These findings illustrate the dynamic tradeoffs that mesopredators make when balancing predation risk and resource acquisition.